Workload, Emotional Intelligence, and Leadership Style : Their Impact on Employee Performance DLHK Kota Kupang - Riwu Kore, Firda R; Yustini, Tien; Alie, Juhaini; Marnisah, Luis; Riwu Kore, Jefirstson R (Perkumpulan Dosen Muda (PDM) Bengkulu, 2025)
Purpose: Analyse and prove the effect of workload, emotional intelligence, and leadership style on the performance of the waste crew of the Kupang City Environmental and Hygiene Service. Methodology: This research is classified as quantitative research. The research population was 103 employees, and the entire population was sampled using the saturated sample technique. The types of research data used are primary and secondary data. Data collection techniques were carried out by observation, closed questionnaire interviews, and documentation. Data analysis using multiple linear regression analysis Results: workload and emotional intelligence partially had a positive and significant effect on performance. Performance is not influenced by leadership style. Performance is simultaneously influenced by workload, emotional intelligence, and leadership style. The contribution of workload, emotional intelligence, and leadership style is 70.2% to performance, which means the correlation between variables is ‘strong’. Findings: The results of this study indicate that the implementation of workload, emotional intelligence, and leadership style has been in accordance with the needs of the organization, thus having an impact on employee performance. These three variables need to be maintained and increased exogeneity so that they have an endogeneity effect on employee performance. Novelty: This research contributes to developing comprehensive human resource management science and further research in this field. Originality: Improving employee performance in government organizations can be done by simultaneously paying attention to aspects of workload, emotional intelligence, and leadership style. Conclusion: Employee performance at the Kupang City DLHK is influenced by workload, emotional intelligence, and leadership style. Type of Paper: Empirical research paper.